A rare case of spontaneous bladder wall abscess mimicking bladder tumour in young women - Alfarizi, Zico Yusuf; Subekti, Eko; Danarto; Yuri, Prahara (BMC urology, 2024)
Abscess of the bladder wall is a rare urological disorder, with a few cases recorded in the literature. The finding of a bladder wall mass via computed tomography (CT) imaging in a visiting patient is the subject of this report. A 37-year-old woman with persistent pain in the suprapubic area and lower urinary tract symptoms was examined as a case study. Through a CT scan revealed an inhomogeneous structure in the anteroinferior part of the right bladder. A cystoscopy procedure followed by transurethral resection was performed to remove the mass, which was found to be an abscess. A Foley catheter with irrigation was administered after surgery, and the patient goes home in three days. the patient had no symptoms or discomfort in the lower urinary tract after follow-up. Despite the rarity of bladder wall abscesses, cystoscopy can be used to aid diagnosis. Transurethral resection of bladder wall can reduce the mass and eliminate the possibility of malignancy.